Indigestible cellulose and lignin in determining feces production and apparent digestibility in horses - doi: 10.4025/actascianimsci.v34i3.10577 - Kátia de Oliveira; Ciniro Costa; Carla Maris Machado Bittar; Vanessa Pillon dos Santos; Vinícius Antonio Baptista Oliveira; Janaina Carolina de Sá (Acta Scientiarum. Animal Sciences, 2012)
Four crossbred geldings were used in a randomized blocks experimental design. The objective was to study the use of the internal markers indigestible cellulose (iCEL) and indigestible lignin (iLIG), obtained in situ (cattle) or in vivo (equine) to predict nutrient apparent digestibility in horses. Treatments consisted of different methodologies to determine digestibility: direct method with total feces collection (TC), and indirect method using internal markers iCEL and iLIG obtained either by in situ incubation in bovine rumen or in vivo (IV) using the mobile nylon bag (MNB) technique in horses. Feces production was 2.80 kg in DM, and average recovery rate (p > 0.05) was 101%. Nutrient digestibility coefficient (p > 0.05) estimates were adequately predicted by iCEL and iLIG, obtained in situ or in vivo, with average values of 52.63, 54.17, 64.90, 43.73 and 98.28% for dry matter, organic matter, crude protein, neutral detergent fiber and starch, respectively. It can be concluded that iCEL and iLIG may be obtained in vivo by MNB in horses consuming a forage-concentrate diet, to predict nutrient digestibility coefficients.